Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Certainly! To solve this problem, we need to determine the inverse of the given logical statement. Here’s a detailed, step-by-step breakdown:
Given statement:
[tex]\[ \sim q \rightarrow \sim r \][/tex]
This statement reads as "if not [tex]\( q \)[/tex], then not [tex]\( r \)[/tex]".
### Step-by-Step Process to Find the Inverse:
1. Understand the Components of the Statement:
- The hypothesis (or antecedent) is [tex]\( \sim q \)[/tex].
- The conclusion (or consequent) is [tex]\( \sim r \)[/tex].
2. Formulate the Inverse:
- The inverse of a conditional statement [tex]\( p \rightarrow q \)[/tex] is formed by negating both the hypothesis and the conclusion.
- Thus, the inverse of [tex]\( \sim q \rightarrow \sim r \)[/tex] requires us to negate [tex]\( \sim q \)[/tex] and [tex]\( \sim r \)[/tex]:
- Negate [tex]\( \sim q \)[/tex], which gives us [tex]\( q \)[/tex].
- Negate [tex]\( \sim r \)[/tex], which gives us [tex]\( r \)[/tex].
3. Construct the Inverse Statement:
- The inverse of [tex]\( \sim q \rightarrow \sim r \)[/tex] is therefore [tex]\( q \rightarrow r \)[/tex].
- This reads as "if [tex]\( q \)[/tex], then [tex]\( r \)[/tex]".
### Finalize the Answer:
Now, we need to match our result with the given options:
A. [tex]\( r \rightarrow q \)[/tex]
B. [tex]\( \sim r \rightarrow \sim q \)[/tex]
C. [tex]\( q \rightarrow r \)[/tex]
D. [tex]\( q \lor \sim r \)[/tex]
From the constructed inverse statement, we see that the correct answer is:
C. [tex]\( q \rightarrow r \)[/tex]
Given statement:
[tex]\[ \sim q \rightarrow \sim r \][/tex]
This statement reads as "if not [tex]\( q \)[/tex], then not [tex]\( r \)[/tex]".
### Step-by-Step Process to Find the Inverse:
1. Understand the Components of the Statement:
- The hypothesis (or antecedent) is [tex]\( \sim q \)[/tex].
- The conclusion (or consequent) is [tex]\( \sim r \)[/tex].
2. Formulate the Inverse:
- The inverse of a conditional statement [tex]\( p \rightarrow q \)[/tex] is formed by negating both the hypothesis and the conclusion.
- Thus, the inverse of [tex]\( \sim q \rightarrow \sim r \)[/tex] requires us to negate [tex]\( \sim q \)[/tex] and [tex]\( \sim r \)[/tex]:
- Negate [tex]\( \sim q \)[/tex], which gives us [tex]\( q \)[/tex].
- Negate [tex]\( \sim r \)[/tex], which gives us [tex]\( r \)[/tex].
3. Construct the Inverse Statement:
- The inverse of [tex]\( \sim q \rightarrow \sim r \)[/tex] is therefore [tex]\( q \rightarrow r \)[/tex].
- This reads as "if [tex]\( q \)[/tex], then [tex]\( r \)[/tex]".
### Finalize the Answer:
Now, we need to match our result with the given options:
A. [tex]\( r \rightarrow q \)[/tex]
B. [tex]\( \sim r \rightarrow \sim q \)[/tex]
C. [tex]\( q \rightarrow r \)[/tex]
D. [tex]\( q \lor \sim r \)[/tex]
From the constructed inverse statement, we see that the correct answer is:
C. [tex]\( q \rightarrow r \)[/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.